BCL-x(L)/MCL-1 inhibition and RARγ antagonism work cooperatively in human HL60 leukemia cells - Perri, Mariarita (Exp Cell Res, 2014)
The acute promyelocytic leukemia (APL) subtype of acute myeloid leukemia (AML) is characterized by chromosomal translocations that result in fusion proteins, including the promyelocytic leukemia-retinoic acid receptor, alpha fusion protein (PML-RARα). All-trans retinoic acid (atRA) treatment is the standard drug treatment for APL yielding cure rates >80% by activating transcription and proteasomal degradation of retinoic acid receptor, alpha (RARα). Whereas combination therapy with As(2)O(3) has increased survival further, patients that experience relapse and are refractory to atRA and/or As(2)O(3) is a clinically significant problem. BCL-2 family proteins regulate apoptosis and over-expression of anti-apoptotic B-cell leukemia/lymphoma 2 (BCL-2) family proteins has been associated with chemotherapeutic resistance in APL including impairment of the ability of atRA to induce growth arrest and differentiation. Here we investigated the novel BH3 domain mimetic, JY-1-106, which antagonizes the anti-apoptotic BCL-2 family members B-cell lymphoma-extra large (BCL-x(L)) and myeloid cell leukemia-1 (MCL-1) alone and in combination with retinoids including atRA, AM580 (RARα agonist), and SR11253 (RARγ antagonist). JY-1-106 reduced cell viability in HL-60 cells alone and in combination with retinoids. The combination of JY-1-106 and SR11253 had the greatest impact on cell viability by stimulating apoptosis. These studies indicate that dual BCL-x(L)/MCL-1 inhibitors and retinoids could work cooperatively in leukemia treatment.